2018
DOI: 10.1186/s41065-018-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome assembly of brackish water flea Diaphanosoma celebensis based on short-term cadmium and benzo[a]pyrene exposure experiments

Abstract: To develop a brackish water flea as a promising model for marine monitoring, Diaphanosoma celebensis were exposed to two pollutants, cadmium (Cd) and benzo[a]pyrene (BaP), which have different chemical characteristics and distinct modes of metabolic action on aquatic animals. Twenty-four hours after exposure to Cd (2 mg/L) or BaP (25 μg/L), whole body transcriptomes were analyzed. In total, 99.6 Mbp were assembled from nine libraries, resulting in 98,458 transcripts with an N50 of 1883 bp and an average contig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 37 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In fact, in recent studies, the genome and transcriptome of D. celebensis were published 24,25 , leading to their potential use at the molecular level in marine ecotoxicology. However, studies on the validation of reference genes are not explored yet in this species.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in recent studies, the genome and transcriptome of D. celebensis were published 24,25 , leading to their potential use at the molecular level in marine ecotoxicology. However, studies on the validation of reference genes are not explored yet in this species.…”
Section: Introductionmentioning
confidence: 99%
“… 2019 ), environmental toxicology (Kim et al. 2018 ), and other aspects, as one of the non-model organisms in the marine and brackishwater environment. In genus Diaphanosoma , the complete mitochondrial genome of Diaphanosoma dubium has been firstly reported (Liu et al.…”
mentioning
confidence: 99%
“…To date, more than 20 species are retrieved in the genus Diaphanosoma (http://v3.boldsystems.org/index.php/ TaxBrowser_Taxonpage?taxid=5262), whereas Korovchinsky (1989) and Korovchinsky (1993) were firstly to redescribe Diaphanosoma celebensis in tropical Asia. Also, D. celebensis has been used in aquaculture (Segawa and Yang 1987), developmental biology (In et al 2019), environmental toxicology (Kim et al 2018), and other aspects, as one of the non-model organisms in the marine and brackishwater environment. In genus Diaphanosoma, the complete mitochondrial genome of Diaphanosoma dubium has been firstly reported (Liu et al 2017), but no further studies on the complete mitochondrial genome have been reported from other Diaphanosoma spp.…”
mentioning
confidence: 99%